The Role of Organization Strategy and Management Accounting Innovations on Cost Performance: The Case of Higher Education Institutions - Evi Marlina; Bambang Tjahjadi (Journal of Accounting and Investment, 2021)
Research aims: This study aims to examine the effect of organizational strategy and management accounting innovations (MAI) on cost performance of private Higher Education Institutions (HEIs). Also, this study investigates the management accounting innovations as mediating variable.Design/Methodology/Approach: This study is quantitative research with a survey approach. This study was conducted by involving HEI located in several provinces in Sumatera Island, Indonesia, covering West Sumatra, Riau, Riau Islands, and Jambi. The research respondents were the head of the HEIs’ finance department. Data analysis utilized Structural Equation Model with Partial Least Square approach (SEM-PLS).Research findings: The results showed that HEI strategy and MAI had a positive direct effect on cost performance. However, management accounting innovations could not be mediating variable.Theoretical contribution/Originality: This study contributes to research areas related to strategy, management accounting innovations, and cost performance in HEI sector.Practitioner/Policy implication: Effectiveness and efficiency in managing HEIs funds requires a strategy and management accounting innovations.Limitation/Implication: The research only included HEIs located in the areas of West Sumatra, Riau, Riau Islands, and Jambi.